Correlation between smoking and results of plane coronarography - Jaciubek, Marzena; Krupienicz, Andrzej (Pielęgniarstwo Chirurgiczne i Angiologiczne/Surgical and Vascular Nursing, 2011)
Introduction : Cardio-vascular diseases (CVD) are the reason for about 50% of deaths and, the same time, the most frequent for hospitalization and permanent incapacity for work in Poland. The whole thing is because of the present-day life style: inappropriate nutrition, lack of sufficient physical activity, smoking cigarettes, drinking alcohol, excessive mental strain, arterial hypertension, hypercholesterolemia, etc. According of the World Health Organization smoking cigarettes is the third frequent cause of cardio-vascular diseases. Harmful consequences of smoking have been known for many years. It has not been known to what extent, if any, coronary vessels, contraction and escalation of changes are effected by smoking in plane coronarography. Aim : The aim of the study was to investigate the correlation between smoking and results of plane coronarography. Material and methods : The study was performed in the group of 101 consecutive patients who were hospitalized at cardiology department and hemodynamics in Wojewódzki Szpital Specjalistyczny in Radom. The patients were subjected to the plane coronarography. The study was accompanied by a self-made examining tool – a questionnaire. The results was analyzed statistically using Statistica 6.0, and calculation were made using imparameter tests 2. Results : In the group of the studied patients, taking into account the classification of changes in coronary arteries, statistically essential correlation between the extension of changes in coronary arteries and the age, education, time and the number of cigarettes being smoked during a day. Conclusions : Most of the studied for the plane coronarography smoke or used to smoke (85% of the studied). Doing the research work on a larger scale may be considered useful especially bearing in mind a detailed study of changes in coronary arteries.